Urgensi Implementasi Fundraising Lembaga Amil Zakat Infak, Dan Sedekah Nahdlatul Ulama (LAZISNU) Kabupaten Jember Dalam Meningkatkan Jumlah Pendapatan Dana Di Era Normal Baru - Nita Andriani; Moch. Chotib; Nurul Widyawati Islami Rahayu (Department of Islamic Economics, Postgraduate Program, UIN Kiai Haji Achmad Siddiq, Indonesia, 2022)
Indonesia is a country with one of the largest Muslim populations in the world. The potential for zakat payment is also great. Jember, home to most NU residents, has not been able to make the most of this potential. Especially when economic sector falls during the covid-19 pandemic. Fundraising is an urgent matter for LAZISNU Jember when funds are the soul of an institution. In the new normal period with the right fundraising techniques, LAZISNU Jember can increase its amount of revenues. The current study employed qualitative research methods. The data were collected by interview techniques, observation and documentation. The research was conducted at the Institute for Zakat, Infaq, and Sadaqah of Nahdlatul Ulama (LAZISNU) Jember. The results of this study are: 1) The urgency of fundraising at LAZISNU Jember for the sustainability of LAZISNU programs in Jember, 2) The implementation of LAZISNU fundraising in Jember using fundraising techniques: Direct fundraising and Indirect fundraising and structural strengthening innovation, 3) Supporting factors: Having great potential because only 8 out of 26 MWC were activated, the issuing of decrees from the NU Headquarter, the optimization of publications on www.nu.or.id and social media, the autonomy in managing ZISWAF, and Inclusive LAZISNU Jember. While the inhibiting factors are as follows: the unavailability of a monthly-paid official Amil (someone assigned to take and record the zakat) at LAZISNU Jember, the impracticality of paying zakat during the Covid-19 pandemic in which people must follow strict health protocols, so that most people choose to donate directly to mustahiq (people who deserve zakat).